Functional Outcome Of Percutaneous K-Wires System In Elder Patients With Proximal Humeral Fractures - Waqas Ali; Rahman Rasool Akhtar; Riaz Ahmed; Muhammad Zahid Siddiq; Nisar Ahmad; Muhammad Nadeem Kashmiri (Journal of Rawalpindi Medical College)
Objective: To evaluate the functional outcome of the percutaneous K-wires system in elder patients with proximal humeral fractures.